High glucose-induced imbalance of mitochondria-associated ER membranes function promotes RSC96 cell damage: Glucose imbalance damages RSC96 cells - Fu, Housheng; Xu, Jianbing; Wang, Fei; Wang, Weifu; Wang, Zhongyao (Cellular and Molecular Biology, 2023)
To investigate the effect of high glucose on mitochondrial-related ER membranes (MAMs) in rat Schwann cells (SCs) and the mechanism of cell injury. SCs (RSC96) cells were used as the control group, and RSC96 cells cultured in a high glucose environment for 48 h were set as the experimental group. The level of intracellular calcium was observed by flow cytometry, and ROS levels were detected by DCFH-DA fluorescent probe. The subcellular structure was observed by transmission electron microscopy, focusing on the morphology of mitochondria and endoplasmic reticulum as well as the formation of MAMs. The expression levels of MAMs-related proteins Mfn2, PERK, VDAC1, and IP3R were detected by Western blot. Compared with the control group, after high glucose-induced cells, the level of calcium ion was significantly increased (p<0.01), the level of ROS was significantly increased (p<0.01), mitochondria and endoplasmic reticulum were damaged, and the number of MAMs was increased (p<0.05). Western blot analysis showed that the expression level of Mfn2 was significantly decreased (p<0.01), and the expression levels of PERK, VDAC1, and IP3R were significantly increased (p<0.01). By inducing the imbalance of MAMs function in SCs, high glucose promotes intracellular calcium overload and leads to cell damage.